Innovation, Resources and Economic Growth - Quadrio Curzio, Alberto; Fortis, Marco; Zoboli, Roberto (Springer Berlin Heidelberg, 1994)
The analysis of the interactions between natural resource scarcity, technological innovation and the dynamics of eco- nomic systems has a long-standing tradition in economics. During the 1980s and the early 1990s, a new phase of these interactions initiated under the effects of technological revolution and the problem of the environment. The general concept behind this book is that the issue of natural resou- cesand the environment in relation to economic growth can- not be addressed without due consideration for the effects of technological innovation on thedynamics of economic sy- stems. Technological innovation alone, however, is not a sufficient condition for the sustainability of economic growth. Policies may have a role in solving the internatio- nal distribution problems generated by the non-converging development path of developed and developing countries. In particular, the new international order shaped by the events of the 1980s, made it possible for world management to ad- dress the problems of poverty and the environment
Keywords: R & D/Technology Policy; Environmental Economics; International Economics; Economic policy; Environmental economics; International economics; Ressourcen; Wachstum; Erschöpfbare Ressourcen; Innovation; Wirtschaftswachstum; Knappheit; Natürliche Ressourcen; Weltwirtschaft; Technischer Fortschritt; Aufsatzsammlung